Comparison of transcriptional responses between pathogenic and nonpathogenic hantavirus infections in Syrian hamsters using NanoString. - Rebecca L Brocato (Public Library of Science (PLoS), 2021)
Background Syrian hamsters infected with Andes virus (ANDV) develop a disease that recapitulates many of the salient features of human hantavirus pulmonary syndrome (HPS), including lethality. Infection of hamsters with Hantaan virus (HTNV) results in an asymptomatic, disseminated infection. In order to explore this dichotomy, we examined the transcriptome of ANDV- and HTNV-infected hamsters. Results Using NanoString technology, we examined kinetic transcriptional responses in whole blood collected from ANDV- and HTNV-infected hamsters. Of the 770 genes analyzed, key differences were noted in the kinetics of type I interferon sensing and signaling responses, complement activation, and apoptosis pathways between ANDV- and HTNV-infected hamsters. Conclusions Delayed activation of type I interferon responses in ANDV-infected hamsters represents a potential mechanism that ANDV uses to subvert host immune responses and enhance disease. This is the first genome-wide analysis of hantavirus-infected hamsters and provides insight into potential avenues for therapeutics to hantavirus disease.